Lipoprotein lipase (LpL) on the surface of cardiomyocytes increases lipid uptake and produces a cardiomyopathy - Yagyu, Hiroaki; Chen, Guangping; Yokoyama, Masayoshi; Hirata, Kumiko; Augustus, Ayanna; Kako, Yuko; Seo, Toru; Hu, Yunying; Lutz, E. Peer; Merkel, Martin; Bensadoun, André; Homma, Shunichi; et al. (The Journal of Clinical Investigation, 2003)
Lipoprotein lipase is the principal enzyme that hydrolyzes circulating triglycerides and liberates free fatty acids that can be used as energy by cardiac muscle. Although lipoprotein lipase is expressed by and is found on the surface of cardiomyocytes, its transfer to the luminal surface of endothelial cells is thought to be required for lipoprotein lipase actions. To study whether nontransferable lipoprotein lipase has physiological actions, we placed an α-myosin heavy-chain promoter upstream of a human lipoprotein lipase minigene construct with a glycosylphosphatidylinositol anchoring sequence on the carboxyl terminal region. Hearts of transgenic mice expressed the altered lipoprotein lipase, and the protein localized to the surface of cardiomyocytes. Hearts, but not postheparin plasma, of these mice contained human lipoprotein lipase activity. More lipid accumulated in hearts expressing the transgene; the myocytes were enlarged and exhibited abnormal architecture. Hearts of transgenic mice were dilated, and left ventricular systolic function was impaired. Thus, lipoprotein lipase expressed on the surface of cardiomyocytes can increase lipid uptake and produce cardiomyopathy.